Inferring epidemiological parameters under an infectious phylogeography model with visitor dynamics - Albert C. Soewongsono; Ammon Thompson; Michael J. Landis (Proceedings of the National Academy of Sciences, 2026)
During an outbreak, infectious disease can spread among populations through host movement, potentially fueling local outbreaks with their own epidemiological dynamics. However, it is difficult to know how often infections between populations are transmitted by diseased travelers infecting healthy residents when abroad, rather than by diseased residents infecting healthy travelers, who later return home with the new pathogen. In this paper, we introduce a phylogeographic model where pathogens spread through visitor dynamics, whereby hosts visit other populations through short trips before returning home. To do so, we used the stationary properties of an epidemiological compartment model with visitor dynamics to construct an approximation that is statistically accurate and computationally tractable for phylogenetic modeling. In addition, we derive mathematical properties for the approximating model that provide a sufficient condition under which the approximation remains accurate. We applied our model to empirical infection data and travel statistics from the European SARS-CoV-2 pandemic. Inference under our model suggests that, in the early stages of the outbreak, SARS-CoV-2 was more often “pulled” into the home countries of returning travelers than “pushed” into foreign countries by visitors from abroad. Estimates of host movement-related parameter values under our visitor model suggest that alternative migration models, with trips of indefinite length, may underestimate the magnitude of outbreaks caused by visitors. This study emphasizes the importance of carefully incorporating host movement dynamics into such models.